Y-chromosomal STR variation in Kurds and Arabs population in Iraqi Kurdistan - Fattah, Yousif Mohammed; Mohammed, Ahmed Basheer; Hussien, Nasreen Jalal (International Journal of Research in Medical Sciences, 2019)
Background: The Iraqi Kurdistan local population involves more than eight gatherings of tenants. The Muslim Kurds make up most of the population and after that the Yezidi Kurds. Alternate gatherings incorporate Armenians, Assyrian, Chaldea, Syriacs, and little minority of Arab and Turkmen individuals. Methods: A total of 36 unrelated males from the two population groups in Iraqi Kurdistan: Kurds and Arabs were analyzed for eight Y-chromosome STRs (DYS19, DYS392, DYS437, DYS448, DYS456, DYS458, DYS635 and Y-GATA-H4). Total DNA from blood cells was extracted using DNA extraction Kit. Results: A number of genetic parameters such as mean number of alleles, allele frequency, gene diversity, polymorphic information content (PIC), and genetic distance were calculated using Power Marker V3.25 software. The DYS458 had the highest diversity (GD: 0.883), while loci DYS456 and Y-GATA-H4 had the lowest (GD: 0.574). The Dendrogram separated the populations into two main clades, the Kurd group and the Arab group except in one case only from the whole population. Conclusions: This study confirms the discriminating power of high-resolution Y-STR typing and provides first primary dataset on Iraqi Kurdistan samples. The comparison of Kurdish and Arab datasets reveals an interesting overall picture of isolation of Kurdish group. The primers DYS19, DYS448, DYS458, and DYS635 can be considered the best for their high PIC power.